2021
DOI: 10.3389/fpls.2021.788104
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Elevated CO2 and Reducing the Source-Sink Ratio by Partial Defoliation on Rice Grain Quality – A 3-Year Free-Air CO2 Enrichment Study

Abstract: Evaluating the impact of increasing CO2 on rice quality is becoming a global concern. However, whether adjusting the source-sink ratio will affect the response of rice grain quality to elevated CO2 concentrations remains unknown. In 2016–2018, we conducted a free-air CO2 enrichment experiment using a popular japonica cultivar grown at ambient and elevated CO2 levels (eCO2, increased by 200 ppm), reducing the source-sink ratio via cutting leaves (LC) at the heading stage, to investigate the effects of eCO2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Grain chalkiness affects the appearance of rice. The imbalance of a source-to-sink under high temperature conditions leads to insufficient grain filling in endosperm cells and disordered enzyme activity, which bring a high grain chalkiness rate [20][21][22][23][24]. In this study, we observed that grains of oslea1b mutants exhibit high chalkiness rates under normal temperatures and chalky endosperm under high temperatures.…”
Section: The Oslea1b Mutants Showed Greater Sensitivity To High Tempe...mentioning
confidence: 63%
“…Grain chalkiness affects the appearance of rice. The imbalance of a source-to-sink under high temperature conditions leads to insufficient grain filling in endosperm cells and disordered enzyme activity, which bring a high grain chalkiness rate [20][21][22][23][24]. In this study, we observed that grains of oslea1b mutants exhibit high chalkiness rates under normal temperatures and chalky endosperm under high temperatures.…”
Section: The Oslea1b Mutants Showed Greater Sensitivity To High Tempe...mentioning
confidence: 63%
“…After the evaluation of the appearance, the milled rice samples were ground into a powder by a vibration disk mill (TS1000, Siebtechnik GmbH, Mülheim, Germany) to further prepare them for subsequent analyses. The starch viscosity of the milled rice and taste score of the cooked rice were determined according to the methods developed by Gao et al [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration in the brown rice was measured using an Infratec™ 1241 grain analyzer (FOSS Tecator, Hillerod, Denmark), which is a near-infrared transmittance (NIT) analyzer. The mineral concentrations in the brown rice were determined using ICP-AES (iCAP6300, Thermo Fisher Scientific, Waltham, MA, USA) after the brown-rice samples were digested using a microwave digestion system (MARS5, CEM Corporation, Matthews, NC, USA) [ 38 ]. The wheat-standard reference material (GBW080684) was used to ensure the precision of the analytical procedures.…”
Section: Methodsmentioning
confidence: 99%
“…eCO 2 levels increase the accumulation of root biomass more than shoot biomass ( Wang et al., 2018 ). A three-year experiment in a free-air CO 2 enrichment (FACE) facility revealed a declining proportion of brown, milled, and head rice under eCO 2 (200 ppm above ambient) relative to aCO 2 ( Gao et al., 2021 ). In addition, the eCO 2 increased grain chalkiness, viscosity, and stickiness but, improving palatability; however, the eCO 2 compromised the processing quality and nutritional attributes such as protein and mineral contents (Ca, Cu and S; except for K) ( Gao et al., 2021 ).…”
Section: Physiological and Molecular Implications Of Individual Stres...mentioning
confidence: 99%
“…A three-year experiment in a free-air CO 2 enrichment (FACE) facility revealed a declining proportion of brown, milled, and head rice under eCO 2 (200 ppm above ambient) relative to aCO 2 ( Gao et al., 2021 ). In addition, the eCO 2 increased grain chalkiness, viscosity, and stickiness but, improving palatability; however, the eCO 2 compromised the processing quality and nutritional attributes such as protein and mineral contents (Ca, Cu and S; except for K) ( Gao et al., 2021 ). A comparative study at eCO 2 (700 ppm) improved seedling emergence, C/N ratio, and biomass in two rice genotypes (IR20 and ADT46).…”
Section: Physiological and Molecular Implications Of Individual Stres...mentioning
confidence: 99%